Epigallocatechin-3-gallate alleviates gestational stress-induced postpartum anxiety and depression-like behaviors in mice by downregulating semaphorin3A and promoting GSK3β phosphorylation in the hippocampus - Xu, Fang; Wu, Hui; Xie, Linghua; Chen, Qing; Xu, Qi; Sun, Lihong; Li, Hua; Xie, Jiaqian; Chen, Xinzhong (Frontiers in Molecular Neuroscience, 2023)
Postpartum depression (PPD) is a common neuropsychiatric disorder characterized by depression and comorbid anxiety during the postpartum period. Currently, PPD is difficult to treat because of its elusive mechanisms. Epigallocatechin-3-gallate (EGCG), a primary component of tea polyphenols, is reported to have neuroprotective effects on emotional disorders through anti-inflammatory and anti-apoptotic functions. However, whether EGCG affects PPD is still unknown and the underlying mechanism has not yet been established comprehensively. Here, we constructed a PPD animal model by applying gestational stress to pregnant mice. We showed that gestational stress induced anxiety and depressive-like behaviors during the postpartum period, which could be alleviated by EGCG treatment. Besides, gestational stress also decreased the expression of hippocampal c-Fos, suggesting the role of hippocampus in PPD-like behaviors. Importantly, gestational stress increased the expression of hippocampal Semaphorin3A (Sema3A) and inhibited the phosphorylation of GSK3β, which could be reversed by systemic administration of EGCG. In conclusion, the anti-anxiety and anti-depression action of EGCG in PPD mice may be involved in the downregulation of Sema3A and the upregulation of phosphorylated GSK3β in the hippocampus. Our findings indicated the potential role of EGCG in alleviating postpartum anxiety and depressive symptoms.